GE_GERICHTE P/12018/2020 vom 11. Dezember 2025 - GE Cour de justice (2025)
ACCUSATION;DISPOSITIONS PÉNALES DE LA LSTUP;FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL) | LStup.19.al1.letb; LStup.19.al2.leta; CPP.9; CP.47; CP.66.ala